Post Diplôme 1995 - 1996 : Samuel Bianchini, Martial Chmielina, Jean-Guillaume Gallais, Marion Galut, Eva Maria Garcia Collado, Olliver Moreels, Mariella Mosler, Asier Pérez-González, Sabdam, Piotr Wojcik. - Latil, J.C; Raynaud, Patrick; Coignet, Jean-Gabriel; École Régionale des Beaux-Arts de Nantes, Nantes (Nantes : Ecole Régionale des Beaux-Arts de Nantes, 1996)
Bianchini, Samuel ; Chmielina, Martial ; Gallais, Jean-Guillaume ; Galut, Marion ; Garcia Collado, Eva Maria ; Moreels, Ollivier ; Mosler, Mariella ; Pérez-Gonzalez ; Sabdam ; Wojcik, Piotr
Cycle Post Diplôme 1995/1996 à Nantes
kunstcatalogus